Raymond Williams en español: La traducción como una contribución a mayor justicia social en procesos de democratización - Juan Gómez, Blanca (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
This paper analyzes the extent to which the translation of Raymond Williams’ texts in Spanish-speaking countries – understood as a cultural process and a social phenomenon – helps foster social justice. To this end, it discusses a bibliographic analysis of existing Spanish-language translations of Raymond Williams’ texts with regard to their publication circumstances (sociopolitical contexts, agendas and agency of the actors involved). In so doing, it distinguishes three phases in the translation of Williams’ work, shaped by democratization processes in Spain and Argentina. Drawing on Sen’s conceptual framework (2009/2010) around the idea of justice, it argues that the process of publishing specific translations to promote social justice is not one of steady advancement, but rather made up of progress, stagnation and setback in different areas, though always with the ultimate goal of reducing injustice. Resumen En este artículo se analiza en qué medida la traducción de textos de Raymond Williams en el ámbito hispanohablante, entendida como fenómeno social y proceso cultural, contribuye a la justicia social. Para ello, vinculamos un análisis bibliográfico de las traducciones al español de textos de Williams publicadas hasta la fecha con sus circunstancias (contextos sociopolíticos, agendas y agencia de los actores implicados), de forma que distinguimos tres fases en la traducción de Williams en procesos de democratización en España y Argentina. Mediante el marco conceptual de Sen (2009/2010) en torno a la idea de justicia, abordamos en cada fase lo que supone la publicación de traducciones seleccionadas a la hora de avanzar hacia mayor justicia social. Defendemos que no se trata de un progreso homogéneo, sino que se dan avances, estancamientos y retrocesos en determinados ámbitos, aunque el objetivo último sea la reducción de injusticias.